Seismic, structural, and individual factors associated with earthquake related injury. Issue 1 (1st March 2003) - Peek-Asa, C; Ramirez, M; Seligson, H; Shoaf, K
Abstract : Background: Earthquakes cause thousands of deaths worldwide every year, and systematic study of the causes of these deaths can lead to their prevention. Few studies have examined how multiple types of risk factors are related to physical injury during an earthquake. Methods: A population based case-control study was conducted to examine how individual characteristics, building characteristics, and seismic features of the 1994 Northridge, California, earthquake contributed to physical injury. Cases included fatal and hospital-admitted injuries caused by the earthquake. Controls were drawn from a population based phone survey of county residents. Cases were individually matched to two sets of controls: one matched by age and gender and one matched by location at the time of the earthquake. Results: Individuals over age 65 had 2.9 times the risk of injury as younger people (95% confidence interval (CI) 1.2 to 7.4) and women had a 2.4 times greater risk than men (95% CI 1.2 to 5.1). Location in multiple unit residential and commercial structures each led to increased injury risk compared with single unit residential structures, but the exact estimate varied depending on the control group used. With every increase in ground motion of 10%g, injury risk increased 2.2 times (95% CI 1.6 to 3.3). Conclusions: Controlling for other factors, it was found that individual, building, and seismic characteristics were independently predictive of increased injury risk. Prevention and preparedness efforts should focus on each of these as potential points of intervention.